Alternativas de topologias retificadoras para aerogeradores síncronos a ímã permanente de baixa potência - Freitas, Tiara Rodrigues Smarssaro de (2015)
Two controlled rectifier topologies applied to low power wind energy conversion system with permanent magnet synchronous generator are presented. For low power or stand-alone operation systems, where the energy from wind generation is a significant part of the total power system, generators and converters have the role of maintaining the grid’s voltage and frequency constant, despite the fluctuations of the wind turbine. In variable speed permanent magnet synchronous generator (PMSG), the preferred solution has been a conversion on two stages: AC-DC-AC. Several converter topologies have been explored, but kind of this conversion has many controlled elements, most of them with 6 controlled switches in AC-DC conversion, making it difficult and more expensive its control; each new topology introduces new aspects and always looking for a converter that best suits the system with minimally influence to the quality of power generation. The topologies presented in the literature are effective for the high power levels, but when it comes to systems with lower power levels, simpler converters (single or three controlled switches) can serve the purpose of rectification with a lower cost and without the conversion quality been reduced. The contribution of this thesis is the development of a new SEPIC rectifier topology using three controlled switches, and the analysis and new application of an existing resonant buck topology, with a single controlled switch, to wind energy system. They are simpler rectifying solutions, applied to low power wind generation based on permanent magnet synchronous generator, offering simplicity and control facility. The converter’s project, the equations that define them, the simulation and experimental results for each converter are presented. It was verified that both topologies could achieve high power-factor and low harmonic distortion employing only one single gate signal, on a wide range of wind speed with no current’s generator closed loop control.